Influência da taxa de carregamento orgânico na degradação anaeróbia da vinhaça em reator de leito fluidizado - Siqueira, Laura Maria (2008)
In this work, the mesophilic anaerobic degradation (35 ºC) of the sugar cane vinasse was studied in an anaerobic fluidized bed reactor (RALF) for 255 days. The reactor, built in acrylic and with a total volume of 4,192 cm3, was filled with polystyrene particles as a means support, occupying 70 % of the total volume, and operated with hydraulic retention time (TDH) of 24 h. The inoculum used was granular sludge taken from a upflow anaerobic sludge blanket reactor (UASB) treating poultry slaughterhouse wastewater. Mixed must vinasse collected in three lots from Usina da Serra (Ibaté/SP) was used in the feed of the reactor. Biomass adaptation to diluted vinasse, with COD of 5,000 mg/L, occurred very fast (14 days) in the reactor itself. Vinasse average concentrations treated were 2,273; 4,891; 8,192; 10,353; 15,244 and 20,073 mg/L with applied organic load rates (OLRs) of 3.33, 6.68, 10.33, 14.44, 19.87 and 26.19 kg/m3.d and reduction efficiency of COD of 53, 67, 59, 66, 70 and 51 % respectively. The effluent pH remained between 7.8 and 8.6 throughout the research. The alkalinity concentrations to bicarbonate (AB) and total volatile acids (TVA) increased with the increase of OLR ranging between 918 mgCaCO3/L and 7,275 mgCaCO3/L and, 365 mgHAc/L and 3,146 mgHAc/L, respectively. The productivity of biogas in the reactor reached 5.37 m3/m3.d with applied OLR of 25.32 kg/m3.d. The methanogenic activity experiments (AME) revealed possible predominance of hydrogenotrophic methanogen. Opticum microscopic exams made it possible to verify the presence of methanogenic Methanosarcina-like archaea during the inoculum adaptation, selection and predominance taking place over the reactor operation of bacillus, coccus and methanogenic Methanosaeta-like archaea. This way it was observed the importance of the vinasse treatment, for besides the improvement of the quality improvement of the effluent to be land disposed, treated and buffered, it also generated a lot of energy (biogas).